Ni Tradicional, ni Proteico: Carrera Docente en las Facultades Empresariales - Soares De Medeiros, Luciane; Pauli, Jandir; Gallon, Shalimar (REICE. Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación, 2022)
The Brazilian educational sector has undergone sharp changes when the private sector began to contribute significantly to the expansion of the offer of higher education. The change in the regulatory framework contributed to the emergence of so-called Entrepreneurial Faculties (FEs), which, unlike universities, offered education without the obligation and actions in research and extension, changing the work structure and, consequently, the career. This study aims to understand the career orientation dilemmas experienced by professors of the EFs. The problematization was made from the theoretical framework that differentiates two types of career: traditional and Protean. A qualitative study was conducted with semi-structured interviews with teachers of these institutions, analyzed through content analysis. The results show that teachers seek to broaden the institutional bond for the development of their careers in the traditional sense but perceive little space for this in the Entrepreneurial Faculties, requiring a constant career reframing to adapt them to the reality of these organizations. The results show that the nature of the work relationship in Brazilian FEs follows a trend already pointed out in international studies on the negative effects of the work structure on the formation of the professors' identity and their satisfaction with the teaching career.